Effects of increasing GleptoForte dosage in newborn pigs on sow and litter performance - Braun, Michaela; Williams, Hayden E.; Jones, Cassandra K.; DeRouchey, Joel M.; Tokach, Michael D.; Woodworth, Jason C.; Goodband, Robert D.; Dritz, Steven S.; Holtcamp, A. (My University, 2017)
The objective of this study was to determine effectiveness of Gleptoforte when considering ADG, BW, and blood parameters of newborn pigs. A total of 336 newborn pigs (DNA 241×600, initially 3.83 ± 0.14lb BW) from 28 litters were used in a 21d farrowing study evaluating the effects of increasing Gleptoforte dosage on suckling pig performance and blood parameters. A total of 28 litters were utilized with number of pigs per sow equalized on each day of farrowing. On d3 after birth all piglets were weighed and six barrows and six gilts per litter were allotted to treatment for a total of 56 piglets per treatment. Treatments consisted of increasing levels of Gleptoforte from 0, 50, 100, 150, 200, or 200mg plus a 100mg booster at d11 post farrowing. Piglets were weighed on d 3, 11, and 21 to calculate ADG during farrowing. All barrows were utilized for blood collection via jugular venipuncture on d 3 (day of processing), d11, and weaning (d21). Blood criteria measured included: Hemoglobin (Hgb), Hematocrit (Hct), Serum Fe, and Total Iron Binding Capacity (TIBC). Throughout the 21d period, BW and ADG of piglets improved (quadratic; P = 0.001) with increasing dosages of Gleptoforte. There was no difference in performance between the 200mg and 200mg + 100mg dosages of Gleptoforte but there was a significant difference for the blood criteria with the 200mg + 100mg having a greater Hgb value. A treatment × day interaction (P=0.001) was observed for both Hgb and Hct with increasing levels (quadratic; P=0.001) as the dosage was increased on d11 and 21 with the 200mg treatment having the highest Hgb and Hct values. A Serum Fe treatment × day interaction (P=0.001) was observed in which there was an increase (quadratic; P=0.001) on d21 with the level increasing as the Gleptoforte dosage level increased. There was no difference in TIBC between the 200mg and 200mg + 100mg treatments. In conclusion, omittance of any supplemental iron injection resulted in the poorest growth performance and blood parameters as expected. However, pigs treated with 100mg of Gleptoforte performed the best with the highest ADG and BW on d 21 while the 200mg + 100mg injection resulted in improved blood parameters but had no impact on growth performance when compared to 200mg alone.
Keywords: Fall 2017